AWARENESS OF GESTATIONAL DIABETES MELLITUS AND ITS DETERMANTS AMONG PREGNANT WOMEN ATTENDING PRIMARY HEALTHCARE CENTERS INAL_ADEL SECTOR BAGHDAD, IRAQ2023-2024 (CAHIERS MAGELLANES-NS, 2024)
Background: Research conducted globally reveals a lack of public knowledge and comprehension about several aspects of diabetes. To minimise the number of complications and co-morbidities in the diabetic population, it is essential to ensure sufficient education, increase awareness, identify difficulties at an earlier stage, and enhance the quality of care.Objectives: To assess the level of awareness of gestational diabetes mellitus, its determenants and its relation to sociodemographic characteristics among pregnant women attending primary healthcare centers in Al adel sector 2023-2024.Methods: A cross sectional study, a randomly selected sample of 400 pregnant women selected conveniently who attended primary health care centers for routine antenatal care visits or for health problems and agree to participate in this study. The study will be conducted in Baghdad provice (alkarkh) in Al-adel sector for PHCs from November 2023 to march 2024.Results: A total of 400 women receiving antenatal care took part in this study. The minimal age of the participants was less than 19 years old, maximum age was 40-49 years old and the mean age was 30 years ±6 years, more than (32% )of the participants had an aged range of 30-39 years, only 44% of the participants had been graduated  and about 38%% of the participants were housewivesConclusions: Only a minority of the individuals demonstrated a significant level of awareness. Advanced age, higher levels of education, employment, having multiple children, being in the third trimester of pregnancy, experiencing previous birth complications, having a history of gestational diabetes or diabetes, and having a family history of diabetes or gestational diabetes were associated with a high level of awareness. A significant number of participants lacked knowledge on the precise diagnostic test and optimal timing for Gestational Diabetes Mellitus (GDM). Target women aged 35 and below, as well as those with a primary education or lower, for health education workshops aimed at increasing their awareness of Gestational Diabetes Mellitus (GDM).